Write the following Arithmetic Sequence using a Recursive Formula: an = -7 + 3(n – 1)
a1 = 3, an = an-1 – 7
a1 = -7, an = an-1 + 3
a1 = -7, an = an+1 + 3
a1 = 3, an = an+1 – 7

Respuesta :

9514 1404 393

Answer:

  (b)  a[1] = -7, a[n] = a[n-1] + 3

Step-by-step explanation:

Comparing the given formula to the general form for the n-th term of an arithmetic sequence ...

  an = a1 +d(n -1)

we see that the first term (a1) is -7, and the common difference (d) is +3.

The recursive version of the sequence definition is ...

  a[1] = a1

  a[n] = a[n-1] +d

So, the appropriate choice is ...

  a[1] = -7, a[n] = a[n-1] +3